Factors associated with compliance with the recommended frequency of postnatal care services in three rural districts of Tanzania. Issue 1 (December 2015) - Kanté, Almamy; Chung, Christine; Larsen, Anna; Exavery, Amon; Tani, Kassimu; Phillips, James
Abstract Background High neonatal mortality persists in Tanzania. Rates of decline are slow, in part because postnatal care (PNC) services for addressing this problem remain severely underutilized. This study assesses factors associated with utilization of PNC among mothers in rural Tanzania. Methods This study analyzed household survey data collected in 2011 to understand health service utilization patterns among women of reproductive age and children less than 5 years of age in the Rufiji, Kilombero, and Ulanga districts of Tanzania. A total of 889 mothers were eligible for the current analysis. Multinomial logistic regression was used to determine factors associated with the likelihood of mothers seeking the WHO recommended PNC visits. Results The percent of newborns and their mothers with full PNC was low (10.4 %). Factors explaining PNC completion were district of residence, ethnic group, pregnancy wantedness, ANC attendance, place of delivery, and any incidence of newborn. Mothers of unwanted pregnancies were less likely to attend PNC services compared to mothers of wanted pregnancies [for at least two PNC: aRRR = 0.57, 95 % CI 0.35–0.94]. Sick newborns were more likely to receive PNC than newborns who were not sick during the first month after childbirth [for at least two PNC, aRRR = 3.52, 95 % CI 2.12–5.86]. Mothers who attended ANC services more frequently were more likely to receive PNC services compared to those who had attended fewer than 2 ANC services [for 1 PNC, aRRR = 1.89, 95 % CI 1.23–2.90]. Mothers who delivered at a health facility were less likely to attend PNC services compared to mothers who delivered outside a facility [for at least 2 PNC: aRRR = 0.42, 95 % CI 0.26–0.76]. Model with interactions between ANC attendance and place of delivery shown that only ANC attendance had a positive and statistically significant effect on PNC visit. Conclusion To achieve the WHO recommended number of PNC in rural Tanzania, our findings suggest the need to provide PNC through the community-based primary health care. Efforts to improve coverage of PNC should include expanding health education and counseling during childbirth and neonatal period to more effectively advocate PNC for newborns perceived to be healthy.